Qualimetry of financial risks in the system of economic security of an enterprise - Hmyria, Viktoriia; Kucherenko, Volodymyr (Management and Entrepreneurship: Trends of Development, 2020)
The relevance of the development of enterprises of Ukraine is characterized by the presence of a significant number of factors that negatively affect the enterprises themselves and their functioning as part of the state. These factors include: the national economy, the instability of tax and regulatory legislation, inflation, unavailability of credit, increased competition, the decrease in the level of investment activity of enterprises and regions, the slowdown of the national payment turnover, the growing number of unprofitable enterprises. The effect of these factors appears in the movement of material and financial flows and leads to significant losses, which in turn adversely affects the economic security of enterprises. The aim of the research is financial risk qualimetry in the system of economic security of enterprise and the development of proposals to improve economic security by minimizing the financial risks. Methodology. In the scientific study following methods were used – analysis (assessing indicators of financial stability and liquidity of the enterprise), synthesis (in determining the impact of components of financial risk in the overall structure of financial risk), Boolean method (in the justification of the main problems associated with the occurrence of financial risk, and its impact on economic security), generalization (in revealing the essence of economic categories “financial risk”, “economic security”). Results. An important step of this work is to determine advantages, disadvantages, conditions for minimizing financial risks in the system of economic security of the enterprise. Conclusions. In the course of the study, the financial risk assessment of Ilyich Iron and Steel Works and its impact on the economic security of the enterprise were researched. The economic boom of the metallurgical plant, industrial regions and the development of industries that coexist together or depend on the metallurgical business depend on the way the enterprise works today. The scientific importance of the article is the possibility to develop enterprise policy to minimize financial risks and ensure economic security. The value of the research lies in the fact that it is necessary to pay attention to the system of risk management in the enterprise and to provide human resources, which will conduct assessment of financial risks, as well as develop effective measures to minimize financial risks and ensure economic security in the economic environment.JEL Classification: G32; D21.